2015
DOI: 10.1016/j.ijid.2014.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin intermediate-Resistant Staphylococcus aureus (VISA) Isolated from a patient who never received Vancomycin treatment

Abstract: This is the first report of VISA found in central China from a patient who had never received vancomycin treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…For the penicillin binding protein encoded by the gene pbp2 , a SNP led to a significant amino acid substitution from the non-polar amino acid glycine to the basic amino acid arginine, which might have influenced the protein structure and thus its activity. Although, this specific mutation has not been previously described in the literature, the overexpression of pbp2 has been implicated in vancomycin-intermediate S. aureus (VISA) phenotype by several studies, demonstrating smaller colony size, lower growth rates, thicker cell walls, decreased lysostaphin susceptibility, and decreased beta-hemolysis 22 25 . Furthermore, the 534 bp deletion in the DHH domain of the GGDEF domain protein containing phosphodiesterase (GdpP) may contribute to the observed phenotypic alterations by impairment of enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…For the penicillin binding protein encoded by the gene pbp2 , a SNP led to a significant amino acid substitution from the non-polar amino acid glycine to the basic amino acid arginine, which might have influenced the protein structure and thus its activity. Although, this specific mutation has not been previously described in the literature, the overexpression of pbp2 has been implicated in vancomycin-intermediate S. aureus (VISA) phenotype by several studies, demonstrating smaller colony size, lower growth rates, thicker cell walls, decreased lysostaphin susceptibility, and decreased beta-hemolysis 22 25 . Furthermore, the 534 bp deletion in the DHH domain of the GGDEF domain protein containing phosphodiesterase (GdpP) may contribute to the observed phenotypic alterations by impairment of enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…VISA strains with a heterogeneous genetic background were reported in several studies from Iran [ 1 ], India [ 40 ], US [ 38 ], Bangladesh [ 42 ], New Zealand [ 39 ] and China [ 43 ]. There is not enough information about the prevalence rate of VISA strains in Iran; however, in 2005, Saderi et al reported the prevalence rate of 1.8% for VISA isolated from clinical samples based on the evaluation of four teaching hospitals in Tehran [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because the high failure rate of vancomycin treatment for MRSA infections is associated with higher vancomycin MICs, the CLSI reduced the vancomycin susceptibility breakpoint for S. aureus from MIC value of 4–2 mg/L to improve the predictive susceptibility result (CLSI, 2016). In China, although VRSA is not by far found, the prevalence of hVRSA was more than 10% (Sun et al, 2009) and VISA has been reported (Zhang et al, 2013; Zhu et al, 2015). The elevated vancomycin MICs among MRSA clinical isolates in China should be of concern.…”
Section: Introductionmentioning
confidence: 99%